Sarcasm in the Young Sheldon Finale: Tabacaru-based analysis - Adani Nur Sabrina; Raden Roro Shinta Felisia (Universitas Merdeka Malang, 2026)
This study investigates the sarcasm in the television series Young Sheldon using the typology proposed by Sabina Tabacaru. While previous studies have examined sarcasm in social media and television discourse, limited attention has been given to the use of sarcasm in Young Sheldon, particularly through a multimodal perspective based on Tabacaru’s framework. Employing a qualitative content analysis approach, the study analyzed sarcastic utterances collected from all episodes of the series’ final season through processes of identification, classification, and contextual interpretation based on the proposed typology. The findings show that sarcasm is realized through various strategies, including antithesis, repetitive statement, explicitation, metonymic inferencing, metaphor, shift of focus, reasoning, and rhetorical question. The analysis also reveals overlapping categories, such as a rhetorical question combined with exaggeration, and sarcasm reinforced by non-verbal cues. These findings demonstrate that sarcasm operates as a complex and multi-layered phenomenon, involving both verbal and non-verbal elements. This study contributes to pragmatic studies by providing insight into the multimodal realization of sarcasm in televised discourse.